1996
DOI: 10.1046/j.1365-2141.1996.280814.x
|View full text |Cite
|
Sign up to set email alerts
|

The thromboxane mimetic, U‐46619, induces the aggregation of fish thrombocytes

Abstract: Fish blood contains nucleated cells termed thrombocytes which are thought to be functionally analogous to mammalian platelets. The present study was undertaken to assess the aggregatory response of peripheral blood thrombocytes from the rainbow trout, Oncorhynchus mykiss. Incubation of Percoll density gradient purified thrombocytes with the thromboxane A2 mimetic, U-46619 (0.03-10 microM), alone or in the presence of human or trout fibrinogen, elicited a dose-dependent aggregatory response. A greater amount of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 19 publications
0
19
0
Order By: Relevance
“…The phagocytic activity of fish thrombocytes has been reported earlier (Hill and Rowley 1996;Slierendrecht et al 1995;Burrows et al 2001;Stosik et al (2001;Kolmam et al (2003). Therefore, the thrombocytes of H. brachysoma can act as blood phagocytes that form one of the protective barriers and may be considered true digesting cells in fish because of the presence of PER and specific esterase enzymes, although more investigations are needed to prove this.…”
Section: Discussionmentioning
confidence: 72%
“…The phagocytic activity of fish thrombocytes has been reported earlier (Hill and Rowley 1996;Slierendrecht et al 1995;Burrows et al 2001;Stosik et al (2001;Kolmam et al (2003). Therefore, the thrombocytes of H. brachysoma can act as blood phagocytes that form one of the protective barriers and may be considered true digesting cells in fish because of the presence of PER and specific esterase enzymes, although more investigations are needed to prove this.…”
Section: Discussionmentioning
confidence: 72%
“…Thrombocytes, in addition to participating in defence through phagocytosis (Hill & Rowley, 1996; Burrows et al , 2001; Tavares‐Dias & Moraes, 2004), are also required for haemostatic plug or fibrin clot (Hill & Rowley, 1996) and they support such energy‐requiring functions, as clot retraction, even though blood glucose may be less readily available (Hayhoe & Quaglino, 1994). Hence, it is necessary to maintain large glucose reserves (Hayhoe & Quaglino, 1994) in the form of glycogen granules (Ueda et al , 2001; Tavares‐Dias & Moraes, 2004; Tavares‐Dias et al , 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies suggest that morphological variability between TC occurs in response to specific physiological conditions (Hill & Rowley, ). Phagocytic activity is broadly recognized as a function of the leukocytes (Silva et al , ) but it has also been suggested that TCs have a role in this immune response (Hill & Rowley, ; Burrows et al , ; Tavares‐Dias et al , ; Shigdar et al , ; Silva et al , ). In this study, the fact that the TC displayed ultrastructural showing vacuolar content being released through canaliculi, suggests that the content may be a product of phagocytic activity (Hill & Rowley, ).…”
Section: Discussionmentioning
confidence: 98%
“…Phagocytic activity is broadly recognized as a function of the leukocytes (Silva et al , ) but it has also been suggested that TCs have a role in this immune response (Hill & Rowley, ; Burrows et al , ; Tavares‐Dias et al , ; Shigdar et al , ; Silva et al , ). In this study, the fact that the TC displayed ultrastructural showing vacuolar content being released through canaliculi, suggests that the content may be a product of phagocytic activity (Hill & Rowley, ). These observations may support the hypothesis that TCs possess an active role in phagocytic activity (Burrows et al , ; Tavares‐Dias et al , ; Zexia et al , ; Silva et al , ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation